Analysis of students' mathematical problem solving ability in solving minimum competency assessment questions on algebra content - Listia; Milla; Riski; Djamilah, Soraya (Balai Publikasi Indonesia, 2025)
Problem solving ability is a mathematical ability that students must have in learning mathematics. Mathematical problem solving in algebraic material is a problem that must be solved using algebraic methods, in solving it there are many obstacles that cause students to make mistakes in the problem solving process. This study aims to analyze the mathematical problem solving ability of VIII grade students in solving Minimum Competency Assessment questions on algebra content. This research uses qualitative research methods. The research instruments used test questions and interviews. The test questions given were AKM with algebra content. The test questions given to class VIII students at SMP Negeri 1 Mandastana totaling 44 people. Furthermore, with the purposive sampling method, 2 students who had different answers were taken to be interviewed as validation of the answers that had been done. The results of this study on question number 1 student A was able to fulfill stages (1), (2), (3), and (4) while student B only fulfilled stages (1), (3), and (4), then on question number 2 student A only fulfilled stages (1), (3) and (4) while student B was only able to fulfill stages (3) and (4).